Unified Performance Analysis of Near and Far User in Downlink NOMA System over η - μ Fading Channel - Mukhtar, Shaika (Array, 2021)
The non-orthogonal multiple access (NOMA) scheme is considered as a frontier technology to cater the requirements of 5G and beyond 5G (B5G) communication systems. To fully exploit the essence of NOMA, it is very important to explore the behavior of NOMA users over the most realistic nonhomogenous fading conditions. In this paper, we derive unified closed-form expressions of the basic performance metrics of the NOMA users. Their performance is evaluated in terms of average bit error rate (ABER), average channel capacity (ACC) and outage probability (OP) over η−μ fading channel. These expressions are in terms of popular functions, such as Meijer G-function and Gauss hypergeometric function, leading to their versatile use in analytical research. Unlike the existing outage probability expressions in terms of Yacoub integral, the derived expressions are easier to implement in software packages like MATLAB. Moreover, we compare the obtained results with a reference system, consisting of genie-aided NOMA system. We interpret that genie-aided performance results provide benchmark bounds for the metrics. Extensive simulations are carried out to validate the derived analytical expressions.